Analysis of Consumer Value Perceptions & Preferences Towards Important Attributes of Frozen Food - Packaged Meatballs In The Bandung City Market - Budiono Budiono; Hartoyo Hartoyo; Mochammad Mukti Ali (Dinasti Publisher, 2024)
Frozen food products have spread widely on the market, either in the form of food ingredients (frozen harvest) or food that has been pre-processed (then frozen). Frozen food is the choice of many people who don't have much free time to cook food. There are already many businesses around frozen food in Indonesia, both in production, distribution and retail sales. One type of frozen food is packaged meatballs. Packaged meatballs are a type of food that is quite popular in Indonesia. There is still a big opportunity to run a frozen food business in Indonesia because the Indonesian population is very high and increases every year. The impact of the Covid-19 pandemic has also affected people's lifestyles, BPS data shows that the highest online sales were for food and beverages, which rose sharply by 1070% from sales in January 2020. Currently, competition between producers is increasingly competitive. To win the competition, companies need to know perception values, preferences and consumer behavior in decision purchasing as a basis for determining marketing strategy. Perception Consumer values , preferences and behavior need to be analyzed, because they cannot be controlled directly by the company. Information on consumer behavior was obtained from research results in traditional markets in the city of Bandung and then analyzed abstractionally and descriptively analyzed.